PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KEPEMILIKAN INSTITUSIONAL - Igmaniar Rakhman; Herry Laksito (Diponegoro Journal of Accounting, 2017)
This study aims to examine the impact of the disclosure of corporate social responsibility (CSRD) to the institutional ownership. This study used secondary data. The population in this study consisted of all manufacturing companies listed in Indonesia Stock Exchange in 2012 - 2015. The sampling method in this research is purposive sampling, and the number of samples in this study were 60 companies. This study used the technique of multiple linear regression analysis. The empirical results of this study show that CSRD, dimensions employee relations and dimension product has a positive and significant effect to institutional ownership. While dimension of community and institutional ownership has not had a significant relationship, and the environmental dimension has a negative and significant relationship with institutional ownership.